An Interrogation into Strategy-Technology Linkage at the Department of Immigration Services, Kenya - Mutua, James, W.; Machuki, Vincent, N. (European Scientific Journal, ESJ, 2018)
There exists a debate on the nature of strategy-technology linkage. Consensus is lacking on whether strategy informs technology, whether technology informs strategy, whether strategy and technology develop independently but match at a later stage, and whether there is no linkage between strategy and technology. This study aimed to find out the extant nature of strategy-technology linkage at the Department of Immigration Services, Kenya. Through a case study research design, primary data were obtained through personal interviews using a structured interview guide. The interviewees were top level managers comprising of the Director of Immigration Services and Assistant Directors of Immigration Services in charge of regions namely: Coast, Eastern, North Eastern, South Rift/Nairobi, North Rift/Western and Nyanza. The study also made use of secondary data from documents in the Department. The data gathered were then analyzed using thematic content analysis. The findings revealed presence of strategytechnology linkage at the Department of Immigration Services, Kenya. The nature cuts across the four thematic areas, but leans more towards strategy informing technology. Incidences supportive of the finding that technology informs strategy, strategy and technology develop independently but match at a later stage and no linkage between strategy and strategy were found but not as recurrent as those of strategy informing technology. The study findings largely support postulations of Configuration and Resource Based theories. The study concludes that strategy informs technology at the Department of Immigration Services, Kenya. For policy making, the study recommends the Department of Immigration Services expends more effort to develop a robust strategy that will inform appropriate technology with selective juxtapositions of technology informing strategy where necessary. For practice, the study recommends strategy-technology linkage that fits the environmental setting with a keen eye on the ever changing environment. The study acknowledged limitations on the contextual setting, design, data collection and analysis methods. The design was a case study which means findings might not be generalized. Data collection was through interviews and analysis was through content analysis, both viewed as largely subjective. Interviews were administered to only the top management within the department. Lower cadres were not represented. The study suggests for further research on the subject through different contextual settings, different designs and different instruments.